Death weavers [compact disc, unabridged] - Mull, Brandon, 1974- (Mull, Brandon, 1974- Five Kingdoms, 2016)
Cole and his friends have made it to the fourth of the five kingdoms that comprise the Outskirts - Necronum, land of the dead. New allies and new dangers await.